Antioxidant activity of Dianthus chinensis L. flowers processed by ionizing radiation - Koike, Amanda (2018)
Edible flowers are increasingly used in culinary preparations, which require new approaches to improve their conservation and safety. Irradiation treatment is safe and an effective alternative for food conservation, guaranteeing food quality, increasing shelf-life and disinfestation. This technology offers a versatile way to get good quality food while reducing post-harvest losses. Dianthus chinensis L. flowers, popularly known as Chinese pink, are widely used in culinary preparations, being also acknowledged for their bioactive components and antioxidant properties. The purpose of this study was to evaluate the antioxidant activity of D. chinensis flowers submitted to electron beam and gamma irradiation at 0, 0.5, 0.8 and 1 kGy. The antioxidant properties were evaluated through the 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity, reducing power and β-carotene bleaching inhibition assays. Total phenolics were determined by the Folin-Ciocalteu assay. The antioxidant activity was higher for irradiated samples, especially those treated with 0.5 and 0.8 kGy, independently of the radiation source, which showed the highest capacity to inhibit β-carotene bleaching inhibition. Accordingly, the applied irradiation treatments seemed to represent feasible technology to preserve the quality of edible flower petals, being able to improve the antioxidant activity